Modelos pedagógicos y su influencia en el proceso de enseñanza-aprendizaje de los niños del subnivel inicial uno de la Unidad Educativa Francisco Huerta Rendón, cantón Babahoyo, Provincia de Los Ríos - Morán Romero, Madelen Xiomara (2022)
The present investigation was carried out with the purpose of analyzing the influence of the pedagogical models in the teaching-learning process of the children of the Initial Sublevel One of the Educational Unit "Francisco Huerta Rendón", an institution that is located in the Canton Babahoyo, Province of the Rivers. The problem lies in the lack of information and implementation of the pedagogical models in the educational institution, determining how these influence the teaching-learning process of the children of the Initial Sublevel One of said institution. On the other hand, to carry out this research, descriptive research was used as a scientific basis and for its development, the qualitative method was also used as a resolution to the problem of the study, together with the use of a research design. non-experimental, also emphasizing that the data collection process was carried out or was carried out through the survey technique with its respective instrument, the questionnaire addressed to parents, allowing the foundation of the research carried out and the establishment of final conclusions and recommendations. Finally, it can be mentioned that this research provided timely and effective information about the influence of pedagogical models in the teaching-learning process of the children of the Initial Sublevel One, ensuring that the children acquire an adequate development of their skills and knowledge.